HASIL BELAJAR KOGNITIF IPA FISIKA SISWA MELALUI PENERAPAN STRATEGI METAKOGNITIF PADA MATERI ALAT OPTIK KELAS VIII MTs HAYATUL ISLAMIYAH PANGEAN - Windy Delvia Delvia; Zulhelmi '; Muhammad Sahal Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The purpose of this research is to describe the results of cognitive learning physicsstudents through the application of metacognitive strategy in optics tool material. The subjects are the student’s of MTs Hayatul Islamiyah class VIII in academic year 2013/2014. Data collection instrument in this research is the cognitive achievement test which consists of test items totaling 15 points multiple choice questions. Analysis of the data in this research is a descriptive analysis to see an overview of cognitive learning result of students using the criteria of absorption, the effectiveness of learning, mastery of learning students and mastery of the objective of learning. From the analysis of data showed: the average absorption is 76,05% with the category of good, the average of effectiveness learning is 76,05% with the category is effective, mastery of learning students is 59,26 % and mastery of the objective of learning is 73,33%. To sum up learning using the application of metacognitive strategy in optics tool material of class VIII MTs Hayatul Islamiyah Pangean could provide positive effect to their absorption. Key Words :Cognitive Learning Result, Metacognitive strategy, Optic Tools.